Uzbek Proverbs Containing Currencies: Diachronic Analysis - Abdullaeva, Nargiza (Tautosakos darbai, 2026)
A diachronic analysis of proverbs provides scientifically valuable results that help us to understand not only the message of the proverb, but also the original meanings of the components, such as words for currencies, from the nation’s non-recent and recent history, including that of the Uzbek nation. Currency words are special with different functions in the structures and meanings of several Uzbek proverbs, which are often seen or heard in contemporary communication in Uzbek society. In addition, finding equivalents in English expands the scope of the Uzbek language, mentality, culture and history to a number of other countries. This paper is devoted to the investigation of Uzbek national proverbs that have the names of ancient (miri, hemir, paqir, kepak, chaqa) and much more contemporary (pul, tiyin, so‘m) currencies in their structures. More specifically, 26 Uzbek proverbs were chosen according to their currency components, and analysed in chronological order taking the approximate usage period of the currency into account. Furthermore, the aims of the research are to identify currency words, especially ancient ones, that are seen in proverbial structures to learn the history and original meanings of these currency words and to determine the functions of names of currencies as culturemes, i.e. conceptual metaphors and/or kernels of proverbs. Having analysed Uzbek proverbs that include currency words diachronically, a questionnaire was sent to Uzbek teachers and students in order to study the usage frequency of Uzbek proverbs containing currency words. Consequently, the questionnaire was useful to show the essential role of various ancient and contemporary currency names in the linguistic characteristics of the Uzbek national proverbs.